A Noble‐Transition Alloy Excels at Hot‐Carrier Generation in the Near Infrared. Issue 23 (29th April 2020) - Stofela, Sara K. F.; Kizilkaya, Orhan; Diroll, Benjamin T.; Leite, Tiago R.; Taheri, Mohammad M.; Willis, Daniel E.; Baxter, Jason B.; Shelton, William A.; Sprunger, Phillip T.; McPeak, Kevin M.
Abstract: Above‐equilibrium "hot"‐carrier generation in metals is a promising route to convert photons into electrical charge for efficient near‐infrared optoelectronics. However, metals that offer both hot‐carrier generation in the near‐infrared and sufficient carrier lifetimes remain elusive. Alloys can offer emergent properties and new design strategies compared to pure metals. Here, it is shown that a noble‐transition alloy, Au x Pd1− x, outperforms its constituent metals concerning generation and lifetime of hot carriers when excited in the near‐infrared. At optical fiber wavelengths (e.g., 1550 nm), Au50 Pd50 provides a 20‐fold increase in the number of ≈0.8 eV hot holes, compared to Au, and a threefold increase in the carrier lifetime, compared to Pd. The discovery that noble‐transition alloys can excel at hot‐carrier generation reveals a new material platform for near‐infrared optoelectronic devices. Abstract : A noble‐transition alloy, Au x Pd1− x, is demonstrated to excel at generating above‐equilibrium "hot" carriers under near‐infrared excitation. Au50 Pd50 provides a 20‐fold increase in the number of ≈0.8 eV hot holes, compared to Au, and a threefold increase in the carrier lifetime, compared to Pd.